Man holding a book - Unknown:::Creator::::::::::::
Photograph shows a man who may be Doris Menendez's father standing next to a table with Chinese looking decorations on it including a small bell and a table runner. He is dressed in Chinese clothing and is holding a book with Chinese characters.